2012
DOI: 10.2323/jgam.58.129
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of <I>Alteromonas macleodii</I> strains reflects their deep/surface habitation rather than geographical distribution

Abstract: The phenotypic, chemotaxonomic and genetic peculiarities of 5 deep strains of Alteromonas macleodii (isolated from Adriatic and Ionian Sea water from a depth of 1,000-3,500 m) and 5 strains of the same species isolated from the surface layer of Aegean, Andaman, Black Sea and Atlantic Ocean water near the British shore have been studied. Electron microscopy has shown that the deep strains' cells were, on average, two times longer (2.1±0.2×0.7±0.1 µm) than the surface strains' (1.1±0.1×0.6±0.1 µm). Using fatty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…This was supported by our rep-PCR DNA fingerprints and further identification on the basis of the 16S rDNA, as we recovered Alteromonas sp. from both eastern and western Mediterranean waters at respective depths of 250 m and 200 m. Other authors describe the significant presence of this marine organism in samples from the Atlantic (Klochko et al, 2012), and in many other tropical and temperate seas (García-Martínez et al, 2002). The genus Pseudoalteromonas is common to the marine environment, including seawater, algae, and marine invertebrates (Baumann et al, 1972(Baumann et al, , 1984Baumann and Baumann, 1981;Gauthier and Breittmayer, 1992;Sawabe et al, 2000).…”
Section: Discussionmentioning
confidence: 91%
“…This was supported by our rep-PCR DNA fingerprints and further identification on the basis of the 16S rDNA, as we recovered Alteromonas sp. from both eastern and western Mediterranean waters at respective depths of 250 m and 200 m. Other authors describe the significant presence of this marine organism in samples from the Atlantic (Klochko et al, 2012), and in many other tropical and temperate seas (García-Martínez et al, 2002). The genus Pseudoalteromonas is common to the marine environment, including seawater, algae, and marine invertebrates (Baumann et al, 1972(Baumann et al, , 1984Baumann and Baumann, 1981;Gauthier and Breittmayer, 1992;Sawabe et al, 2000).…”
Section: Discussionmentioning
confidence: 91%
“…In this context, comparative genomics demonstrated that strains EC673 and BS11 do not possess an AS, despite having the conserved genomic boundaries at the respective AS insertion sites and being clearly affiliated with the surface clade (http://onlinelibrary.wiley.com/doi/10.1111/1462-2920.12862/suppinfo). This microdiversity mirrors strain‐specific variations in flexible genomic islands (López‐Pérez et al ., ) and suggests the presence of ‘sub‐ecotypes’ within the surface and deep clade (Klochko et al ., ), which possibly reflect specific adaptations to a certain habitat or niche.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the marine bacterium Alteromonas macleodii are found to be generally clustered with the depth in the water column from which the isolate originated [50]. Klochko et al found that peculiarities of A. macleodii strains reflected their deep/surface habitation rather than geographical distribution [51]. Similarly, Tarasov et al exposed significant differences between deep and shallow-water hydrothermal vent communities [52].…”
Section: Discussionmentioning
confidence: 99%